Hubungan Celebrity Worship dengan Identitas Diri Remaja Penggemar K-Pop - Vita Famia Sari; Adi Isworo; Suyanta Suyanta; Erna Erawati (JURNAL KEPERAWATAN MERSI, 2019)
Background - Teenager is one phase that is traversed by humans. Nowadays, teenagers facing technological developments rapidly that can make it easier to access the internet, one of them is Korean culture. The tendency to follow K-Pop idols causes fans to have celebrity worship. The impact of celebrity worship such as being extra vagant, willing to do anything for their idol, has a crisis of identity, and following the style of their idol. Objective - This study was conducted to determine the relationship between celebrity worship and the self-identity of teenagers K-Pop fans. Methods - The approach of this study used a quantitative method by correlation study design. The sampling technique used was purposive sampling that involved 80 teenage respondents aged 12-20 years. The data was taken by using the questionnaire method. Results - The results of this study indicate that there is no relationship between celebrity worship and the self-identity of teenagers K-Pop fans because the results of the Pearson test in p value of 0.837 (p value 0.05). Conclusion - There is no relationship between celebrity worship and the self-identity of teenagers K- Pop fans.